2023
DOI: 10.1021/jacsau.3c00081
|View full text |Cite
|
Sign up to set email alerts
|

Design of Microstructure-Engineered Polymers for Energy and Environmental Conservation

Abstract: With the ever-growing demand for sustainability, designing polymeric materials using readily accessible feedstocks provides potential solutions to address the challenges in energy and environmental conservation. Complementing the prevailing strategy of varying chemical composition, engineering microstructures of polymer chains by precisely controlling their chain length distribution, main chain regio-/stereoregularity, monomer or segment sequence, and architecture creates a powerful toolbox to rapidly access d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 275 publications
(415 reference statements)
0
3
0
Order By: Relevance
“…Among the diverse topological polymers, hyperbranched polymers, including hyperbranched polyesters (HBPEs), have garnered considerable interest due to their distinctive 3D globular structures, intriguing physical and chemical properties, and abundant functional end groups. , Unlike their perfectly symmetrical counterparts, dendrimers, , hyperbranched polymers can be produced on a commercially viable scale using a streamlined one-step process while preserving key features of dendrimers, such as excellent solubility, low solution/melt viscosity (which facilitates processing), and a high degree of functionality. These attributes render them appealing for various biological applications such as drug delivery, tissue engineering, and bioimaging. , Furthermore, branching is a pervasive and crucial phenomenon that can lead to accelerated, more efficient transfer, dissipation, and distribution of energy or matter …”
Section: Introductionmentioning
confidence: 99%
“…Among the diverse topological polymers, hyperbranched polymers, including hyperbranched polyesters (HBPEs), have garnered considerable interest due to their distinctive 3D globular structures, intriguing physical and chemical properties, and abundant functional end groups. , Unlike their perfectly symmetrical counterparts, dendrimers, , hyperbranched polymers can be produced on a commercially viable scale using a streamlined one-step process while preserving key features of dendrimers, such as excellent solubility, low solution/melt viscosity (which facilitates processing), and a high degree of functionality. These attributes render them appealing for various biological applications such as drug delivery, tissue engineering, and bioimaging. , Furthermore, branching is a pervasive and crucial phenomenon that can lead to accelerated, more efficient transfer, dissipation, and distribution of energy or matter …”
Section: Introductionmentioning
confidence: 99%
“…They are stacked together by weak van der Waals forces. MoS 2 /C with monolayers has been proven to be a promising material for a wide range of energy storage applications including supercapacitors (SCs) and secondary batteries. SCs combine the technical characteristics of common capacitors and secondary batteries, providing higher specific energy than common capacitors, higher specific power than secondary batteries, and longer cycle life. For example, Han et al designed an independent core–shell heterostructure supported on carbon nanotube fibers by anchoring MoS 2 nanosheets on nanowires (MoS 2 @TiN/CNTF) as the anode of AASCs, which has great advantages in wearable water-based SCs. Abbas et al reported “one-step” liquid phase coexfoliation of graphene (G) and MoS 2 together, i.e., graphene nanoplatelet (GNP)/MoS 2 using high-temperature ultrasonication and gelatin.…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, reversible-deactivation radical polymerization (RDRP) has revolutionized polymerization techniques by introducing a reversible activation/deactivation step into radical polymerization, among which nitroxide-mediated polymerization (NMP), atom transfer radical polymerization (ATRP), , and reversible addition–fragmentation chain transfer (RAFT) polymerization are the three most frequently used ones. Several other RDRP systems have also been developed, which share similar kinetic behaviors with NMP, ATRP, or RAFT polymerizations, for example, organometallic-mediated radical polymerization (OMRP), organotellurium-mediated radical polymerization (TERP), and iodine transfer polymerization (ITP). , RDRP allows the precision synthesis of polymers with predictable M n and low Đ (<1.5) at gentler conditions than that of LAP, , and the manipulation of Đ is a significant topic for probing the dispersity–property relationships of the polymer materials in the RDRP community. ,, …”
Section: Introductionmentioning
confidence: 99%